2015
DOI: 10.1371/journal.pone.0133622
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study on Serum Levels of 10 Trace Elements in Schizophrenia

Abstract: The etiology and pathophysiology of schizophrenia remain obscure. This study explored the associations between schizophrenia risk and serum levels of 10 trace elements. A 1:1 matched case-control study was conducted and matched by age and sex. Blood samples were collected to determine the concentrations of nickel, molybdenum, arsenic, aluminum, chromium, manganese, selenium, copper, iron and zinc by an inductively coupled plasma-mass spectrometry. The conditional logistic regression model was used to analyze t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 35 publications
4
31
0
1
Order By: Relevance
“… 75 Much more remains to be learned to fully appreciate the relevance and significance of blood GPx activity along the various stages of the disease. The fact that low level of selenium is a risk factor for schizophrenia 76 supports the need for further studies on GPx in patients. Indeed, GPx are selenium-containing enzymes whose activities depend on this essential micronutrient.…”
Section: Discussionmentioning
confidence: 97%
“… 75 Much more remains to be learned to fully appreciate the relevance and significance of blood GPx activity along the various stages of the disease. The fact that low level of selenium is a risk factor for schizophrenia 76 supports the need for further studies on GPx in patients. Indeed, GPx are selenium-containing enzymes whose activities depend on this essential micronutrient.…”
Section: Discussionmentioning
confidence: 97%
“…Malfunctions related to any of these enzymes due to decreases or increases in Cu may explain the origin of mental illness. Liu et al 33 found lower concentrations of Cu in SCZ serum and they associated such decreases with a risk of SCZ, while Gonzalez‐Estecha et al 34 found higher Cu levels in the serum of BD patients, associating such increases with BD pathophysiology.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have shown that dysregulation of Cu adversely influences biological processes of several psychiatric disorders including SZ [21][22][23][24][25][26][27][28][29][30], BD [25,[31][32][33], and MD [25,28,34]. The reduced [28,30,35,36], elevated [21][22][23][26][27][28][29]37,38], and unaltered [25,28,39,40] Cu levels in SZ patients have been mentioned in different studies. Higher Cu concentrations were reported in the course of the BD [41].…”
Section: Discussionmentioning
confidence: 99%